Sex-specific and concentration-dependent influence of Cremophor RH 40 on ampicillin absorption via its effect on intestinal membrane transporters in rats - Yin, Heyue; Shao, Haibin; Liu, Jing; Qin, Yujia; Deng, Wenbin (PLOS ONE, 2022)
Pharmaceutical excipients are the basic materials and important components of pharmaceutical preparations, and play an important role in improving the efficacy of drugs and reducing adverse reactions. Therefore, selecting suitable excipients for dosage form is an important step in formulation development. An increasing number of studies have revealed that the traditionally regarded "inert" excipients can, however, influence the bioavailability of drugs. Moreover, these effects on the bioavailability of drugs caused by pharmaceutical excipients may differ in between males and females. In this study, the in situ effect of the widely-used pharmaceutical excipient Cremophor RH 40 spanning from 0.001% to 0.1% on the intestinal absorption of ampicillin in male and female rats using closed-loop models was investigated. Cremophor RH 40 ranging from 0.03% to 0.07% increased the absorption of ampicillin in females, however, was decreased in male rats. The mechanism of such an effect on drug absorption is suggested to be due to the interaction between Cremophor RH 40 and two main membrane transporters P-gp and PepT1. Cremophor RH 40 altered the PepT1 protein content in a sex-dependent manner, showing an increase in female rats but a decrease in males. No modification on the PepT1 mRNA abundance was found with Cremophor RH 40, indicating that the excipient may regulate the protein recruitment of the plasma membrane from the preformed cytoplasm pool to alter the PepT1 function. This influence, however, may differ between males and females. As such, the study herein shows that supposedly inert excipient Cremophor RH 40 can influence membrane fluidity, uptake and efflux transporters in a sex- and concentration-dependent manner. These findings, therefore, highlight the need for sex-specific studies in the application of solubilizing excipients in drug formulation development.